ANALYSIS OF CRIMINAL LIABILITY OF PERPETRATORS OF ELECTION CRIME VOTE MANIPULATION (Decision Number: 120/Pid.Sus/2024/PN Kot) - Kholifah Nuzulul Hikmah; Heni Siswanto; Erna Dewi (Utan Kayu Publishing, 2025)
This study specifically examines the manipulation of election recapitulation documents by election officials in Tanggamus Regency (Decision No. 120/Pid.Sus/2024/PN Kot). This case violates fundamental principles of election administration, highlighting the need for strict law enforcement. The research uses a normative juridical approach, focusing on statutory regulations, legal doctrines, and court decisions. Primary data include relevant laws such as the 1945 Constitution, Election Law No. 7 of 2017, and the Criminal Code, while secondary data comprise court rulings and related literature. Data were collected through document analysis and processed using the Miles, Huberman, and Saldana model. The study concludes that criminal law enforcement is essential to uphold justice, protect human dignity, and ensure compliance with election laws. The manipulated votes meet the elements of a criminal offense, with the defendants deliberately violating election regulations by altering official vote recapitulation records. The court imposed penalties, including imprisonment and fines, emphasizing no justification or excuse for the offenses. Thus, vote manipulation is a serious crime requiring firm sanctions to deter violations, maintain electoral justice, and guarantee legal certainty in election administration.